Evaluation of Organoleptic and Nutritional Characteristics of Traditionally Processed Shrimp Products Based on Its Quality Grade - Endang Sri Heruwati; Endang Pratiwi; Nur Retnowati (Indonesian Food and Nutrition Progress, 1999)
It is very common that to fit with the market segment, processor produces varied quality grade of product with different prices. However, there is no clue that the quality grade represents the organoleptic and nutritional characteristics of the product. And observation on organoleptic and nutritional characteristics of shrimp crackers (kerupuk udang), paste (petis udang), and cake (terasi udang) obtained from some processor in. Sidoharjo, East Java, have been conducted based on product quality grade. Organoleptic characteristics of the three kinds of product in term of product appearence, taste, odor, and texture were assessed by sensory judgement, white measurement of linear expansion was applied only to fish crackers. Protein, carbohydrate, and ash contents were used as parameters for nutritive value. Result of evaluation revealed that for shrimp crackers, there were differences in protein and carbohydrate content between different quality grades and different prices. It seemed that the quality grade, and product price, which is determined by the processors, could represent the nutritive value in term of protein and carbohydrate content. On the contrary, there were no difference on organoleptic characteristics, ash content, and linear expansion of all grades of products. For shrimp paste, there were no significant differences on all quality attributes nor the prices. In this case, the quality grade and price did not represent the organoleptic and nutritional characteristics of the product. As for shrimp cake, differences among the product grade were assessed only on organoleptic characteristics, not the nutritive values. Based on this results, it seems that quality grading by the processor, and so does the product price, did not always represent the organoleptic and nutritional quality of the product. To overcome this, Indonesian Food and Nutrition Progress, 1999 Vol 6, no. 2 it is now the time to develop and implement a process and product standardization of traditional processed shrimp, especially shrimp crackers, paste, and cake in Indonesia, as to give assurance to the consumers to get appropriate organoleptic and nutritional quality of the product equal to the amount of money they paid.